La imagen de la mujer en la propaganda de consumo como referente para una propuesta de instalación escultórica. - Guarnizo Alvarez, Kathy Cecilia (2018)
The project THE IMAGE OF WOMEN IN THE PROPAGANDA OF CONSUMPTION AS A REFERENCE FOR A PROPOSAL OF SCULPTURAL INSTALLATION is framed in the analysis of theoretical, technical and aesthetic characteristics of the sculptural installation taking as a manager the image of women in the propaganda of consumption, through the appropriate use of expressive resources and elementary technical procedures, contributing in this way with contemporary sculptural alternatives. For the development of the research, analytical, deductive and experimental methods were used to obtain information, analyze it and sustain the sculptural work. The proposal involves the use and experimentation of new materials, determining the interaction and bonding artist - spectator. The installation proposal will be disseminated through digital and printed media